Will the skill-premium in the Netherlands rise in the next decades? - Arnaud Dupuy (Institute for the Study of Labor (IZA), 2007)
While the skill-premium has been rising sharply in the US and the UK for 20 years, the Dutch skill-premium decreased for much of that period and only started to rise in the early 90s. In this paper, we investigate whether the Dutch skill-premium will rise in the next decades. To answer this question, we forecast the skill-premium using the Katz and Murphy (1992) and the Krusell et al. (2000) models. The Katz and Murphy model (KM) explains demand shifts by skill-biased technological change in unobservable variables captured by a time trend. In contrast, the Krusell et al. model (KORV) explains demand shifts by (observable) changes in the capital stock under a capital-skill complementarity technology. The results show that while the KM model predicts that the skill-premium will have increased by 30% in 2020, based on realistic predictions of the stock of capital, the KORV model predicts that the skill-premium will remain between -5% and +5% of its 1996 level.
urn:nbn:de:101:1-2008041096
Keywords: 330; Qualifikation; Bildungsertrag; Technischer Fortschritt; Komplementärgut; Kapital; Niederlande